Doda Idi : Tradisi Aceh Terhadap Pendidikan Karakter Anak Usia Dini - Veryawan; Arie Dwi Ningsih; Ade Tursina (JURNAL BUNGA RAMPAI USIA EMAS, 2025)
Traditions are activities that have been carried out for generations and have messages that are beneficial to a society. The process of educating children through the doda idi tradition is the delivery of educational messages that parents chant to their children when they are going to sleep. This education is the beginning of character formation as an adult where children will record all forms of knowledge gained during their golden age. This research aims to determine the form of children's education through the traditional process of doda idi, where Acehnese children are accustomed to going to sleep with doda idi songs and knowing the values contained in doda idi poetry. The method in this research uses library research methods, namely a series of research relating to library data collection methods, or research whose research objects are explored through various library information. The research results show that children's education through the doda idi tradition is very effective for forming children's character because it has messages that are full of moral and religious values. This form of education is carried out through a habituation process when the child is put to sleep in a swing with doda idi poetry sung by his parents.